Rearranging the Bird’s Nest Fungi: molecular review of internal clades in Cyathus (Nidulariaceae, Basidiomycota) - Rhudson Henrique Santos Ferreira da Cruz; Jefferson dos Santos Góis; Paulo Marinho; Iuri Goulart Baseia; Kentaro Hosaka (IMA Fungus)
Abstract The genus Cyathus was established in 1768, but more in-depth taxonomic studies with the group only occurred after 1844. In the following years, changes in the infrageneric classification of Cyathus were proposed based mainly on morphology. With advances in phylogenetic studies, the morphological classifications were tested and a new subdivision into three groups was proposed in 2007. Based on the last two classifications, this work aims to expand and understand the internal phylogenetic relationships among the fungi of the genus Cyathus and examine how these relationships are reflected in the taxonomic classification, through molecular analyses covering most of the species in the group, based on materials obtained from type specimens deposited in major fungal collections worldwide, besides expanding sampling with tropical species. Molecular analyses followed the protocols available in the literature, including the design of specific primers for Cyathus. In the phylogenetic analysis, using Maximum Parsimony and Bayesian methods, sequences of ITS and LSU regions from 41 samples of 39 species of Cyathus, 26 were placed with some nomenclatural types. The monophyly of Cyathus was confirmed with maximum support in both tests, and the infrageneric groups of the most recent classification were unchanged, but the clade striatum showed segregation into four groups and three subgroups. The phylogenetic organization is supported morphological characters, and diagnoses are presented for each group, as well as a dichotomous key for the infrageneric separation.